The nexus between business-investment climate and firm performance in the Middle East and North Africa (MENA) region - Eleftherios Giovanis; Öznur Özdamar Giovanis (Review of Economics and Political Science (REPS), 2022)
Purpose Effective business and investment climate can lead to a higher rate of investment, profits and improved productivity, through the creation of an institutional environment, where the state provides high-quality public goods. This study aims to explore the impact of the business-investment climate on firm performance in a sample of six countries in the Middle East and North Africa (MENA) region and Turkey. Furthermore, we extend our analysis to explore the impact of business-investment climate on the resource misallocation in Egypt and Turkey. Design/methodology/approach The study used fixed effects models to investigate the relationship between the business and investment climate, expressed by the obstacles in state-business relations- and the firm performance, which is measured by the firm's value-added, the labour productivity and the total factor productivity To reduce the endogeneity coming from possible reverse causality and the perceptions about the business climate, an instrumental variables (IV) approach applying the two-stage least squares (2SLS) method was followed. The empirical analysis relies on data derived from the World Bank Enterprise Surveys. Findings Based on estimates, the obstacles in business climate may reduce the firm performance measures by 15-40%. These findings indicate the importance of quality in the business climate and how the improvement in its efficiency can have a very considerable positive impact on firms' performance and thus on the overall economic growth of a country. Originality/value This is the first study exploring the impact of business-investment climate on various measures of the firm performance and the resource misallocation in a large sample of countries in the MENA region.
Keywords: D73; K15; L5; O1; O43; O49; O57; 330; Economic development; Governance; Middle East and North Africa region; Resource misallocation; State business relations; Total factor productivity